자기 활성 세포 분리법과 군체 분리법으로 분리된 건 줄기세포의 자가 재생 능력 및 분화능 효율 비교 - 이모세; 최유림; 윤동석; 이진우; 윤길성; 최우진; 한승환; Lee, Moses; Choi, Yoorim; Yoon, Dong Suk; Lee, Jin Woo; Yoon, Gil Sung; et al. (대한족부족관절학회지, 2014)
Purpose: The purpose of this study is to evaluate the efficacy of mesenchymal stem cell (MSC) isolation by the magnetic-activated cell sorting (MACS) method in tendon tissue-derived cells compared to the colony picking method for isolation of MSCs by picking colony-forming cells. Materials and Methods: Human tendon-derived cells were isolated by enzyme digestion using normal tendon tissues from three donors. We used the magnetic kit and well-known MSC markers (CD90 or CD105) to isolate MSCs in tendon-derived cells using MACS. Cloning cylinders were used to isolate colony-forming cells having MSC characteristics in tendon-derived cells. Colony-forming unit-fibroblast (CFU-F) assay was used to evaluate the self-renewal capacity of cells isolated using the colony picking method or MACS. For comparison of differentiation potentials into osteogenic or adipogenic lineage between two groups, alizarin red S and oil red O staining were performed at 14 days after induction of differentiation in vitro. Results: Flow cytometry results showed that early passage tendon-derived cells expressed CD44 in 99.13%, CD90 in 56.51%, and CD105 in 86.19%. In the CFU-F assay, CD90+ or CD105+ cells isolated with MACS showed larger colony formation in size than cells isolated using the colony picking method. We also observed that CD90+ or CD105+ cells were constantly differentiated into both osteogenic and adipogenic lineages in cells from all donors, whereas cells isolated using the colony picking method were heterogeneous in differentiation potentials to the osteogenic and adipogenic lineages. Conclusion: CD90+ or CD105+ cells isolated using MACS showed superior MSC characteristics in the self-renewal and multi-differentiation capacities compared with cells isolated using the colony picking method.